Sociodemographic characteristics of patients admitted to diyarbakir research, treatment and training centre for substance addiction in children and adolescents and types of substances used - Şimşek, Şeref; Dönmezdil, Süleyman; Kakdaş, Erkan; Özen, Şakir (Journal of Dependence, 2014)
Objective: This study aims to investigate sociodemographic characteristics of the patients admitted to the substance addiction treatment center and types of substances used.Method: Between January 2011 and December 2011, medical files of a total of 258 (245 boys, 13 girls; mean age: 18.11±5 years; range, 8 to 45 years) who were admitted to Research, Treatment and Training Centre for Substance Addiction in Children and Adolescents in Diyarbakir (ÇEMATEM) were retrospectively analyzed.Results: The mean number of siblings was 4.7±2.6. A total of 153 patients (59.3%) were below 18 years of age, while 105 (40.7%) were above 18 years of age. Seventy six patients (29.5%) had a single-parent family. A total of 236 patients (91.5%) had no history of a suicide attempt, while 22 (8.5%) had a history of a suicide attempt once at least. A total of 244 patients (94.6%) had a smoking history, whereas 14 (5.4%) did not smoke. Of patients, 111 (43%) had an alcohol history, whereas 147 (57%) did not. The most common type of substance used was cannabis in 85.3%.Conclusion: Identification of risk factors of substance abuse would be helpful to take precautions against substance abuse and addiction, which is on an increasing trend in this region, as well as to tailor individualized treatment options.
Keywords: substance abuse; substance misuse; marijuana; risk factors